Innowacje produktowe a efektywność przedsiębiorstwa - Czupiał, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper focuses on the management of new product development. It considers the relationship between new products and the efficiency of an enterprise. As a result, it shows that new product development is one of the most common forms of growth strategies. A part of this paper focuses on the various models of new product development that have emerged over the past 50 years. More recent models try to emphazise the importance of the external linkages in the new product development process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 57-67